Outcome of Palliative Care in Cancer Patients in Maharach hospital, Phra Nakhon Si Ayutthaya Province - เที่ยงแก้ว, สุนิดา; สุขีลักษณ์, ประทีป (Journal of Preventive Medicine Association of Thailand, 2018)
Cancer is a cause of suffering to patients and family, so palliative care needs across physical, psychological social and spiritual. The purposes of this quasi-experimental research were to compare the results of palliative care service (measurement used palliative care outcome scale: POS) in 32 cancer patients who admitted to Maharach hospital, Phra Nakhon Si Ayutthaya from June to November 2560 (who had palliative performance scale: PPS 30%) and cancer patients’/family’s satisfaction of palliative care service. The patients were asked to complete the POS before (during the first day-second day of admission) and after next 3-7 days. Data were analyzed and presented by frequency, percentage, mean and standard deviation. Comparison of outcomes between before and after palliative care used paired t-test with statistical significant level at 0.05. The results showed that the average score of POS after palliative care was decreased with statistical significance (before 28.84, after 17.13, p<0.001). The patients and family’s satisfaction of palliative care service were high with statistical significance in physical ( =3.12, 4.24; p<0.001), social and environment ( =3.08, 4.00; p<0.001) and total palliative care nursing ( =3.00, 4.06; p<0.001). The patients and family’s satisfaction of palliative care service were medium in psychological ( =3.30, 3.50; p<0.001) and spiritual ( =2.40, 3.34; p=0.018). It was concluded that this palliative care can improve patients’ outcomes and satisfaction of service. Therefore, this palliative care system should be generalized to all other settings